Unruptured Brain Arteriovenous Malformations: A Systematic Review and Meta-Analysis of Mortality and Morbidity in Aruba-Eligible Studies - Pinheiro, Leon Cleres Penido; Wolak Junior, Mario [UNESP]; Ferreira, Marcio Yuri; Magalhaes, Raphael Bertani; Fernandes, Adriano Yacubian [UNESP]; Paiva, Wellingson Silva; Zanini, Marco Antonio [UNESP]; Marchesan Rodrigues, Maria Aparecida [UNESP] (Elsevier, 2024)
Background: Treating unruptured brain arteriovenous malformations (bAVMs) represent significant challenges, with numerous uncertainties still in debate. The ARUBA trial induced further investigation into optimal management strategies for these lesions. Here, we present a systematic-review and meta-analysis focusing on ARUBA-eligible studies, aiming to correlate patient data with outcomes and discuss key aspects of these studies. Methods: Following PRISMA guidelines, we conducted a systematic-review. Variables analyzed included bAVM Spetzler-Martin (SM) grade, treatment modalities, and outcomes such as mortality and neurological deficits. We compared studies with a minimum of 50% cases classified as SM 1–2 lesions and those with less than 50% in this category. Similarly, a comparison between studies with at least 50% microsurgery-cases and those with less than 50% was performed. We examined correlations between mortality incidence, SM distribution, and treatment modalities. Results: Our analysis included 16 studies with 2.417 patients. The frequency of bAVMs SM-grade 1–2 ranged from 44% to 76%, SM-grade 3 from 19% to 48%, and SM 4–5 from 5 to 23%. Notably, studies with more than 50% cases presenting lesions SM-grade 1–2 presented significantly lower mortality rates than those with less than 50% cases of SM 1–2 lesions (P < 0.001). No significant difference in mortality rates or neurological deficits was identified between studies with more than 50% of microsurgery-cases and those with less than 50%. Conclusions: The analysis revealed that studies with a higher proportion of bAVMs presenting SM 1–2 lesions were associated with lower mortality rates. Mortality did not show a significant association with treatment modalities.
Keywords: Brain arteriovenous malformations; Endovascular surgery; Microneurosurgery; Radiosurgery; Spetzler-Martin classification; Vascular neurosurgery